Penggunaan Relatif Atas Depresiasi yang Dilaporkan dan Pengeluaran Modal Untuk Pengambilan Keputusan Investasi - Widaninggar, Nanda; Sumarni, Murti (Akmenika, 2015)
Investors conducted that earnings was one of the stock’s price indicators. The substitution of accrual basis accounting information to cash basis accounting information was such a big issue since there were much critical ideas across accrual basis accounting information. The aim of this research was to recognize the impact of that substitution, by comparing the earnings in predicting the stock’s price when depreciation was included and when it was substituted by capital expenditure. Linier regression model, the comparation of determination coefficient (R2) between two equations and p-value were used to test the hypothesis and to determine the significance level of the model. This research’s samples were the manufactured companies listed in Indonesia Stock Exchange which was consistenly listed in the crisis period, from 1997-2002 and 2008-2013 and it was found that accrual basis depreciation had more information content than cash basis capital expenditure component that could not indicate the stock’s price.